Evaluasi Virtual Reality Menggunakan Technology Acceptance Model (TAM) Terkait Dunia Metaverse - Ega Mardoyo; Muharman Lubis; Susetyo Bagas Bhaskoro (APIC, 2022)
Abstract - Digital disruption makes innovation and transformational sustainable in the digital world. The Industrial Revolution 4.0 has changed the face of the new digital era with a diverse foundation of new and advanced technologies in it. According to Geissbauer (2016) there are 10 technologies that are the foundation of Industrial Revolution 4.0 i.e. mobile devices, IoT platforms, location detection technologies, advanced human machine interfaces, automation & Fraud Detection, 3D manufacturing, smart sensors, big data analytics & advanced algorithms, Multilever customer interaction and customer profiling, Augmented Reality / wearables / immersive technologies, cloud computing. Virtual Reality as one of the technological foundations in the Industrial Revolution 4.0 has grown rapidly along with the term ‘Metaverse’ echoed by Mark Zuckerberg CEO of Facebook in October 2021. Metaverse itself is identified as a virtual world where all human activities can be done in it. Virtual Reality as one of the components of the Metaverse is an attraction for the industry to start this technology, especially in exhibition activities (Expo). Virtual Reality Expo for SME is one of the important foundations regarding user understanding regarding the introduction of Virtual Reality technology. Therefore, as an advanced technology that is currently rampant, the author conducts research on Virtual Reality Expo using the technology Acceptance Model (TAM).